ISSUES OF INTRODUCTION OF MODERN TECHNOLOGIES IN THE RESOLUTION OF CORPORATE DISPUTES AND THEIR IMPACT ON LEGAL PRACTICE - Abdurakhimov, Shokhrukh (Educational Research in Universal Sciences, 2023)
In recent years, the growing influence of technology on the legal field has been the subject of much interest and debate. This article examines the impact of technology on corporate dispute resolution and the practice of law, highlighting the benefits and challenges arising from the use of technology in these areas. The article begins by exploring how technology has changed the landscape of dispute resolution, including the development of online dispute resolution platforms, the use of artificial intelligence and machine learning in legal decision-making, and the use of blockchain technology to facilitate security. and effective conflict resolution. The article examines the broader implications of these technological developments, including their impact on the legal profession and the justice system in general. Finally, the article concludes with a discussion of the potential future directions of technology and legal practice in corporate dispute resolution and the importance of addressing the ethical and regulatory challenges arising from these developments.